Prediction and minimization of NOx emission in a circulating fluidized bed combustor: A comprehensive mathematical model for CFB combustion. (1st February 2022) - Ke, Xiwei; Engblom, Markus; Yang, Hairui; Brink, Anders; Lyu, JunFu; Zhang, Man; Zhao, Bing
Graphical abstract: Schematics of the CFB combustor (left) and 1-D/1.5-D hybrid CFB model (right). Highlights: A comprehensive 1-D/1.5-D hybrid CFB combustion model is developed. Gas mixing processes in splash zone are considered in 1-D/1.5-D CFB modeling. Homogeneous reaction system is described by a detailed chemical kinetic mechanism. The model is validated against field test data from three commercial CFB boilers. Gas-solid fluidization state has significant impacts on NOx emission. Abstract: A comprehensive 1-dimensional/1.5-dimensional hybrid mathematical model is developed for predicting NOx emission of a circulating fluidized bed (CFB) combustor under broader operating parameters. In this model, the local gas–solid fluidization state and gas/heat transfer conditions in different regions of a CFB combustor are specifically considered. Some two- or three-dimensional problems, such as bubble breakage over dense bed surface, secondary air injection, core-annular flow structure, and particle clusters in freeboard, are also taken into account in 1-D/1.5-D modeling. The detailed chemical kinetic mechanism is creatively used to describe the homogeneous reaction system towards CFB combustion simulation. In addition to operating parameters and fuel-specific inputs, no other model parameters can be trimmed from case to case. This integral CFB model is validated against the field test data obtained from three commercial CFB boilers with different capacities, some of which are first disclosed. Favorable comparisons are obtained between the predicted and measured results, involving particle size distributions, temperature and pressure profiles, and NOx /SO2 emissions. The final NO emission, as well as gas profiles, are somewhat different among the cases, which may be attributed to the discrepancy in boiler structure, fuel properties, and operating conditions. Further sensitivity analysis indicates that the proportion of volatile-N in total fuel-N, char combustion reactivity, and char-NO reactivity significantly impact the NOx emission for CFB combustion. Meanwhile, the gas–solid fluidization state also plays an essential role in the NOx emission and the in-furnace combustion efficiency, such as the gas flow distribution between phases, bubble size, secondary air penetration depth, etc. However, the NOx emission seems insensitive to the particle external gas mass transfer coefficients.